The role of courts in transitional justice : voices from Latin America and Spain - Almqvist, Jessica; Esposito, Carlos D. (Milton Park, Abingdon, Oxon : Routledge, 2011)
'This book examines the role of courts in times of transition. The book focuses on judicial experiences from the Iberoamerican region, in particular Argentina, Chile, Colombia, Spain and Guatemala, exploring the extent to which national courts have been able to shoulder the task of investigating and prosecuting grave crimes such as genocide, crimes against humanity and war crimes, committed in the context of a previous repressive rule or current conflict. The volume contains contributions from judges, prosecutors, and scholarly experts in the region. It offers first-hand experiences and expert findings on crucial issues surrounding the role of the courts including: balancing principles of justice and fundamental concerns about legality and non-retroactivity; security problems facing courts in conflict situations; the immense case load; the role of regional and international courts in aiding their national counterparts; and the cooperation between different and overlapping jurisdictional competences. The book also draws attention to the way in which regional and international courts have come to contribute to the initiation of national judicial processes, above all, through international standard-setting and pressure. It goes on to articulate a philosophical critique of the dominant understandings of transitional justice because it has not paid sufficient attention to criminal justice. In this context, the volume outlines an alternative conceptualisation that seems better equipped to both explain the recent developments towards the'judicialization' of transitional justice politics while, at the same time, also insisting on the continued need for caution and critical reflection on the role of courts in times of transition'--
Introduction / Jessica Almqvist & Carlos Esposito -- Recollections of the international adjudication of cases of massacres: its relevance for transitional justice and beyond / Antonio Augusto Cancado Trindade -- The progressive development of the international law of transitional justice: the role of the inter-American system / Felipe Gonzalez Morales -- The possibility of criminal justice: the Argentinean experience / Ricardo Gil Lavedra -- Chilean transitional justice and the legacy of the de facto regime / Roberto Garreton -- Spain as an example of total oblivion with partial rehabilitation / Alicia Gil Gil -- The challenges posed to the recent investigation of crimes committed during the Spanish Civil War and Francoism / Javier Chinchon Alvarez -- Responding to human rights violations committed during the internal armed conflict in Peru: the limits and advances of Peruvian criminal justice / Yvan Montoya Vivanco -- Many roads to justice: transnational prosecutions and international support for criminal investigations in post-conflict Guatemala / Naomi Roht-Arriaza & Almudena Bernabeu -- The criminal investigation and its relationship to jurisdiction, extradition, cooperation and criminal policy / Susan Kemp -- Colombia as a Sui Generis case / Alejandro Aponte -- Restoring civic confidence through transitional justice / Paul Seils -- The international criminal court: possible contributions of the Rome Statute to judicial processes in transitional societies / Elizabeth Odio Benito -- Conclusion / Carlos Esposito & Jessica Almqvist.
Includes bibliographical references and index.
Keywords: Transitional justice -- Latin America; Justice, Administration of -- Latin America; Courts -- Latin America; Transitional justice -- Spain; Justice, Administration of -- Spain; Courts -- Spain; International criminal law